Finding the right fit: Mock victims' preferences for police interviewer characteristics. Issue 2 (20th March 2021) - Snow, Mark D.; Akca, Davut; Connors, Christina J.; Crough, Quintan; Eastwood, Joseph
Abstract: Victims can provide details necessary to resolve criminal investigations but may be reluctant to come forward and fully disclose an incident to law enforcement. Although evidence‐based interviewing techniques such as rapport‐building have shown promise in increasing cooperation, the potential impact of interviewers' inherent characteristics (e.g., age and gender) on information disclosure has been relatively under examined. We investigated mock sexual assault victims' preferences for various police interviewer characteristics and the impact of these preferences on hypothetical reporting behaviour. Participants rated interviewers' interpersonal skills as highly important. Gender differences were observed, with only female participants consistently reporting that having a same‐gender interviewer was important. Participants also indicated that if they were provided with their preferred interviewer, they would feel more comfortable, provide more detail, and would be more willing to report the offence to police. Our findings suggest that matching interviewees with their preferred interviewers may improve interviewing and investigative outcomes.